Carbon fiber, its manufacturing method, and carbon fiber composite material

By optimizing the production process of carbon fiber, combining high-quality polyacrylonitrile-based carbon fiber precursor fibers and multi-stage heat treatment steps, the problem that carbon fibers in the prior art are difficult to have high strand elastic modules, strand strength and elongation at the same time, and achieving high impact resistance and energy absorption.

JP7655307B2Active Publication Date: 2025-04-02TORAY INDUSTRIES INC

Patent Information

Application Number
JP2022508215
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-19
Filing Date
2021-03-05
Publication Date
2025-04-02
Estimated Expiration
2041-03-05

AI Technical Summary

Technical Problem

The prior art is difficult to improve the elongation and impact resistance of carbon fiber while maintaining high strand elastic modulus and strand strength.

Method used

By controlling the production process of carbon fiber, including the use of high-quality polyacrylonitrile-based carbon fiber precursor fibers, and through a series of flame-resistant, pre-carbonization and carbonization steps, the structure and performance of carbon fibers are optimized to achieve 240-300GPa strand elastic modulus, 2.65% or higher elongation and 95J/mm³ or higher strain energy density.

Benefits of technology

It realizes the high impact resistance and energy absorption capabilities of carbon fiber, while maintaining high strength and appropriate elongation, improving the overall performance of carbon fiber composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007655307000001
    Figure 0007655307000001
Patent Text Reader

Abstract

A carbon fiber wherein the strand elastic modulus is 240-300 GPa, the ductility is 2.65% or greater, and the strain energy density is 95 J / mm3 or greater. The present invention provides a carbon fiber that can improve the impact resistance of a carbon fiber composite material.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a carbon fiber having excellent energy absorption and high elongation, a method for producing the same, and a carbon fiber composite material using the same. [Background technology]

[0002] Polyacrylonitrile carbon fiber is a lightweight material with high strength and high elasticity, making it an essential material for reducing the weight of components. Another characteristic of carbon fiber is that it does not undergo plastic deformation, but rather elastic deformation. Therefore, carbon fiber has the advantage of being able to be used in a wider elongation range than metals, which undergo large plastic deformation.

[0003] In recent years, carbon fiber composite materials are required to be both lightweight and impact resistant. To meet this requirement, the composition of the resin used in the matrix and sizing agents to change the interfacial properties between the carbon fiber and the matrix resin have been investigated.

[0004] Attempts to improve the strand strength or elongation of carbon fibers have been made in the past. In Patent Document 1, precursor fibers are thinned to reduce defects, thereby obtaining carbon fibers with a maximum strand strength of 9.0 GPa (Example 8). Similarly, in Patent Document 2, precursor fibers are thinned and then stretched to obtain carbon fibers with a maximum strand strength of 8.0 GPa (Example 14) and elongation of 2.60% (Comparative Examples 4 and 5). In Patent Document 3, carbon fibers with a maximum strand strength of 8.4 GPa (Example 3) are obtained by increasing the fracture toughness value of the carbon fibers. In Patent Document 4, a carbon fiber with a maximum elongation of 2.68% (Example 15) is obtained by using a technology that does not easily decrease the strand strength even if the single fiber diameter of the carbon fiber is increased. In Patent Document 5, the manufacturing conditions such as polymer, yarn making, and flame retardation are adjusted to aim for high elongation, and a carbon fiber with a maximum elongation of 2.36% (Example 1) is obtained. In Patent Document 6, aiming to maximize the elongation of carbon fiber, the maximum temperature in the carbonization process is lowered, and carbon fiber with a maximum elongation of 2.60% (Example 4) is obtained. Patent Document 7 describes obtaining high-strength, high-elongation carbon fiber by adjusting the surface properties of carbon fiber, but the elongation of the carbon fiber is about 2.1%, which is at the general technical level for high-strength carbon fiber. Patent Document 8 obtains carbon fiber with a maximum elongation of 2.71% (Example 4) by adding boron to a polymer.

[0005] Furthermore, in a study to improve the impact resistance of carbon fiber composite materials, Patent Document 9 adds a modifier to the thermoplastic resin matrix. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Application Publication No. 11-241230 [Patent Document 2] International Publication No. 2008-40963 [Patent Document 3] JP 2017-137614 A [Patent Document 4] International Publication No. 97 / 45576 [Patent Document 5] JP 2008-163537 A [Patent Document 6] JP 2005-256211 A [Patent Document 7] JP 2002-69754 A [Patent Document 8] Japanese Patent Application Publication No. 11-152626 [Patent Document 9] JP 2018-59087 A Summary of the Invention [Problem to be solved by the invention]

[0007] However, the conventional techniques have the following problems.

[0008] In the technology of Patent Document 1, the single fiber diameter of the carbon fiber is small, and the strain energy per single fiber is small. In addition, the strand elastic modulus is high and the elongation is low, so sufficient impact resistance cannot be ensured in a bending stress field.

[0009] The technique of Patent Document 2 has the problem that the single fiber diameter of the carbon fiber is small, the strain energy per single fiber is small, and a satisfactory elongation is not obtained.

[0010] The technique of Patent Document 3 has a problem in that satisfactory elongation is not obtained, and furthermore, since the strand elastic modulus is high, sufficient impact resistance cannot be ensured in a bending stress field.

[0011] In the technology of Patent Document 4, the strand strength and elongation levels are insufficient, and sufficient impact resistance cannot be ensured. In addition, it was not anticipated that both strand strength and elongation would be achieved.

[0012] The technology of Patent Document 5 does not ensure sufficient impact resistance.

[0013] In the technology of Patent Document 6, the strand elastic modulus level was too low, and sufficient impact resistance could not be ensured.

[0014] In the technology of Patent Document 7, the elongation level was too low and sufficient impact resistance could not be ensured.

[0015] Although the technology of Patent Document 8 increases the elongation of carbon fibers, the strand strength is low for those with high elongation, and the concept of strain energy density was not considered, so it was not anticipated that strand strength and elongation would be compatible. Thus, there has not been a carbon fiber that satisfies all of the requirements for single fiber diameter, strand modulus, elongation, and strain energy density.

[0016] Furthermore, in Patent Document 9, although the composition of the thermoplastic resin is designed to improve the impact resistance of the carbon fiber composite material, there is no mention of the mechanical properties of the carbon fiber itself.

[0017] An object of the present invention is to provide a carbon fiber that can improve the impact resistance of a carbon fiber composite material. [Means for solving the problem]

[0018] In order to achieve the above object, the carbon fiber of the present invention has a strand modulus of elasticity of 240 to 300 GPa, an elongation of 2.65% or more, and a strain energy density of 95 J / mm 3 That's all.

[0019] In addition, the method for producing carbon fibers of the present invention comprises the steps of: subjecting polyacrylonitrile-based carbon fiber precursor fibers to a process for producing a carbon fiber having a wavelength of 1,370 cm in the infrared spectrum; -1 Peak intensity at 1,453 cm -1 a first flame-retarding step for 8 to 25 minutes until the ratio of the peak intensities of the fibers obtained in the first flame-retarding step is in the range of 0.98 to 1.10; -1 Peak intensity at 1,453 cm -1 The ratio of the peak intensities is in the range of 0.70 to 0.75, and the peak intensity at 1,370 cm in the infrared spectrum is -1Peak intensity at 1,254 cm -1 a second flame-stabilizing step of flame-stabilizing the fiber obtained in the second flame-stabilizing step for 5 to 14 minutes until the ratio of peak intensities of the fibers to the peak intensities of the fibers reaches a range of 0.50 to 0.65; a pre-carbonizing step of pre-carbonizing the fiber obtained in the second flame-stabilizing step in an inert atmosphere having a maximum temperature of 500 to 1,200°C and a draw ratio of 1.16 to 1.25; a carbonizing step of carbonizing the fiber obtained in the pre-carbonizing step in an inert atmosphere having a maximum temperature of 1,000 to 1,500°C, a maximum temperature treatment time of 20 to 60 seconds, and a temperature rise rate of 0.40 to 1.1°C / sec; and a step of electrolytically surface-treating the fiber obtained in the carbonizing step to obtain carbon fiber. Effect of the Invention

[0020] By using the carbon fiber of the present invention, the impact resistance of a carbon fiber composite material can be improved. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] The inventors focused on the strain energy density of carbon fibers in improving the impact resistance of carbon fiber composite materials. The strain energy density is the area of ​​the stress-strain curve obtained by a tensile property test of a resin-impregnated strand (hereinafter sometimes abbreviated as strand). However, since it is difficult to accurately calculate nonlinearity, in the present invention, the above-mentioned strand strength (MPa = J / mm 3 The approximate value calculated by dividing the product of the strain energy density (-) and the elongation (-) by 2 is taken as the strain energy density. The high strain energy density of carbon fiber is expected to improve the impact resistance of the resulting carbon fiber composite material.

[0022] The carbon fiber of the present invention has a strain energy density of 95 J / mm 3 or more, preferably 100 J / mm 3 More preferably, it is 105 J / mm 3 More preferably, it is 110 J / mm 3 The strain energy density is 95 J / mm 3 Above this level, energy absorption is often sufficient, and there is no upper limit, but 140 J / mm 3In some cases, the value of energy absorption is saturated in the balance with other properties. The strain energy density can be adjusted by controlling the manufacturing conditions of the carbon fiber so as to achieve both strand strength and elongation.

[0023] The carbon fiber of the present invention has a strand modulus of 240 to 300 GPa, preferably 250 to 290 GPa, and more preferably 250 to 280 GPa. The strand modulus is an index showing the resistance to deformation when a load is applied to the carbon fiber. The strand modulus of the carbon fiber can be evaluated according to the tensile test of a resin-impregnated strand described in JIS R7608:2004. The stress-strain curve of the carbon fiber shows a downwardly convex nonlinearity, but in the present invention, the strand modulus in the strain range of 0.1 to 0.6% is used. If the strand modulus is 240 GPa or more, the strain energy density is easily increased. If the strand modulus is 300 GPa or less, the carbon fiber has a high compressive strength and high energy absorption. The strand modulus can be controlled by the maximum temperature in the carbonization process, the heat treatment time at the maximum temperature, the heating rate, the draw ratio, and the like.

[0024] The carbon fiber of the present invention has a strand strength of preferably 7.5 GPa or more, more preferably 7.8 GPa or more, and even more preferably 8.0 GPa or more. The strand strength is an index showing the resistance to breakage when a load is applied to the carbon fiber. The strand strength of the carbon fiber can be evaluated according to the tensile test of a resin-impregnated strand described in JIS R7608:2004. If the strand strength is 7.5 GPa or more, the strain energy density is easily increased. There is no upper limit to the strand strength, but if it is 8.8 GPa, the strain energy density is likely to be at a satisfactory level. The strand strength can be controlled by producing the carbon fiber according to the production method described later, such as suppressing defects and improving the fracture toughness value.

[0025] The carbon fiber of the present invention has an elongation of 2.65% or more, preferably 2.75% or more, more preferably 2.85% or more, and even more preferably 2.95% or more. The elongation of the carbon fiber can be evaluated according to the tensile test of the resin-impregnated strand described in JIS R7608:2004. It is difficult to measure the elongation of the carbon fiber because the stress-strain curve shows nonlinearity, but in this tensile test, the elongation is calculated by dividing the above-mentioned strand strength by the strand elastic modulus. If the elongation is 2.65% or more, it is easy to increase the strain energy density. There is no upper limit to the elongation, but 3.20% is often sufficient to increase the strain energy density. The elongation of the carbon fiber can be adjusted by controlling the manufacturing conditions of the carbon fiber so as to balance the strand strength and the strand elastic modulus.

[0026] The carbon fiber of the present invention has a single fiber diameter of preferably 4.0 μm or more, more preferably 4.5 μm or more, even more preferably 5.0 μm or more, and particularly preferably 5.3 μm or more. The breaking load per single fiber is determined from the strand strength and the single fiber cross-sectional area, so the single fiber diameter affects the breaking load per single fiber. In addition, the larger the single fiber diameter, the higher the single fiber compressive strength of the carbon fiber tends to be, and the greater the energy absorption is likely to be. Therefore, if the single fiber diameter is 4.0 μm or more, the greater the energy absorption is likely to be. If the upper limit of the single fiber diameter is 7.5 μm, sufficient impact resistance can often be ensured. The single fiber diameter of the carbon fiber can be calculated from the total fineness, density, and number of filaments of the carbon fiber. In addition, when the number of filaments is unknown, the carbon fiber can be embedded in resin, the cross section observed with an optical microscope, the cross-sectional area of ​​the single fiber is obtained by image processing, and the cross-sectional area is calculated as the circle equivalent diameter to evaluate the single fiber diameter. If the two measurement methods do not match, the former value is adopted. The monofilament diameter can be controlled by the precursor fiber diameter and the draw ratio in subsequent steps.

[0027] It is important for the carbon fiber of the present invention that the single fiber diameter, strand modulus, elongation and strain energy density all fall within the above ranges in order to enhance the impact resistance of carbon fiber composite materials.

[0028] The carbon fiber of the present invention has a total fineness of preferably 0.8 g / m or more, more preferably 0.9 g / m or more. The total fineness is the mass per meter of the carbon fiber bundle, and is related to the single fiber diameter and number of filaments of the carbon fiber. The higher the total fineness, the easier it is to increase the productivity of the carbon fiber composite material. Therefore, if the total fineness is 0.8 g / m or more, a carbon fiber composite material with excellent impact resistance can be obtained with good productivity. If the total fineness is 2.0 g / m or less, a carbon fiber composite material with an appropriate thickness can be obtained, and as a result, impact resistance can be improved, which is preferable. The total fineness can be controlled by adjusting the single fiber diameter or the number of filaments, but if the number of filaments is too large, uniform production becomes difficult, and the strand strength tends to decrease.

[0029] The carbon fiber of the present invention preferably has a density of 1.75 to 1.85 g / cm 3 The higher the density of carbon fiber, the denser the microstructure, and the greater the strand strength. Therefore, the density is 1.75 g / cm 3 Above this level, the energy absorption is likely to be at a satisfactory level, 1.85g / cm 3 If it is less than this, the elongation is high and the energy absorption is high and easy to maintain. The lower limit of the density is more preferably 1.78 g / cm 3 The upper limit of the density is more preferably 1.83 g / cm 3 The density of the carbon fiber can be controlled by the draw ratio and the heating rate in the carbonization process.

[0030] Next, a method for producing carbon fibers suitable for obtaining the carbon fibers of the present invention will be described.

[0031] Known industrial methods for producing carbon fibers include a flame-retardant process in which polyacrylonitrile-based carbon fiber precursor fibers (hereinafter sometimes abbreviated as precursor fibers) are converted into flame-retardant fibers in an oxidizing atmosphere at 200 to 310°C, a pre-carbonization process in which the precursor fibers are pre-carbonized in an inert atmosphere at 500 to 1,200°C, and a carbonization process in which the precursor fibers are carbonized in an inert atmosphere at 1,000 to 1,500°C.

[0032] A polyacrylonitrile polymer is preferably used as a raw material for producing the precursor fiber. In the present invention, the polyacrylonitrile polymer is a polymer in which acrylonitrile accounts for at least 90 to 100 mol % of the polymer. In producing the precursor fiber, the polyacrylonitrile polymer preferably contains a copolymerization component from the viewpoint of improving strand strength. As a monomer that can be used as the copolymerization component, a monomer containing one or more carboxylic acid groups or amide groups is preferably used from the viewpoint of promoting flame resistance.

[0033] In producing the precursor fiber, either the dry-wet spinning method or the wet spinning method may be used as the spinning method, but it is preferable to use the dry-wet spinning method, which is advantageous in terms of strand strength of the resulting carbon fiber. The spinning process includes a spinning step in which a spinning solution is discharged from a spinneret into a coagulation bath by the dry-wet spinning method, a water washing step in which the fiber obtained in the spinning step is washed in a water bath while being stretched, and a dry heat treatment step in which the fiber obtained in the water washing step is dry-heat treated, and preferably includes a steam drawing step in which the fiber obtained in the dry heat treatment step is steam-drawn as necessary. The order of each step can be appropriately changed. The spinning solution is obtained by dissolving the polyacrylonitrile-based polymer described above in a solvent in which polyacrylonitrile is soluble, such as dimethyl sulfoxide, dimethylformamide, and dimethylacetamide.

[0034] The coagulation bath preferably contains a solvent such as dimethylsulfoxide, dimethylformamide, or dimethylacetamide used as the solvent for the spinning solution, and a so-called coagulation promoter. As the coagulation promoter, a solvent that does not dissolve the polyacrylonitrile polymer and is compatible with the solvent used for the spinning solution can be used. Specifically, it is preferable to use water as the coagulation promoter.

[0035] The washing bath in the washing step is preferably a multi-stage washing bath having a temperature of 30 to 98° C. The draw ratio in the washing step is preferably 2 to 6 times. After that, an oil agent made of silicone or the like is preferably applied to the fibers for the purpose of improving the strand strength. The silicone oil agent preferably contains amino-modified silicone.

[0036] The drying heat treatment step can be carried out by a known method. For example, the drying temperature is 100 to 200°C.

[0037] After the above-mentioned water washing step and dry heat treatment step, steam drawing is carried out as necessary to obtain a precursor fiber suitable for obtaining the carbon fiber of the present invention. The steam drawing is carried out in pressurized steam at a draw ratio of preferably 2 to 6 times.

[0038] In order to increase the strand strength of carbon fiber, the flame-retardant fiber obtained in the flame-retardant process must have a wavelength of 1,370 cm in the infrared spectrum. -1 Peak intensity at 1,453 cm -1 The ratio of the peak intensities of the two peaks is in the range of 0.70 to 0.75, and the peak intensity of the two peaks is 1,370 cm -1 Peak intensity at 1,254 cm -1 It is preferable to control the ratio of the peak intensities of the 1,453 cm -1 The peak at 1,370 cm is derived from alkenes and decreases as the flame resistance increases. -1 Peak and 1,254cm -1The peak at 1,370 cm is due to the flame-retardant structure, and increases as the flame resistance progresses. -1 Peak intensity at 1,453 cm -1 is about 0.63 to 0.69, which indicates that in the flame-retardant process of the present invention, it is preferable that the obtained flame-retardant fiber retains more alkene-derived structures than usual. -1 Peak intensity at 1,254 cm -1 The peak intensity ratio decreases as the flameproofing progresses, and the decrease is particularly large in the initial stage. However, depending on the flameproofing conditions, the peak intensity ratio may not become 0.65 or less even if the time is increased.

[0039] In order to achieve a ratio of these two peak intensities within the desired range, the conditions should be set by focusing mainly on the following: the amount of copolymerization component contained in the polyacrylonitrile polymer constituting the precursor fiber is small, the degree of crystal orientation of the precursor fiber is high, the single fiber fineness of the precursor fiber is small, and the flameproofing temperature is increased in the latter half. -1 Peak intensity at 1,453 cm -1 a first flame-stabilizing step in which the fiber is flame-stabilized for 8 to 25 minutes, preferably 8 to 15 minutes, until the ratio of the peak intensities of -1 Peak intensity at 1,453 cm -1 The ratio of the peak intensities is in the range of 0.70 to 0.75, and the peak intensity at 1,370 cm -1 Peak intensity at 1,254 cm -1 It is preferable to carry out the second flame-stabilization step in two stages, in which the flame-stabilization is carried out for 5 to 14 minutes, preferably 5 to 10 minutes, until the peak intensity ratio reaches a range of 0.50 to 0.65.

[0040] The flame-stabilizing temperature in the first flame-stabilizing step is preferably set to 200 to 250° C., more preferably 230 to 250° C., in order to control it within the above-mentioned infrared spectrum range.

[0041] The stabilization temperature in the second stabilization step is higher than that in the first stabilization step. In order to shorten the stabilization time in the second stabilization step, the stabilization temperature may be adjusted to be high, but the appropriate stabilization temperature depends on the characteristics of the precursor fiber. In order to control the stabilization temperature within the above-mentioned infrared spectrum range, it is preferable to set the stabilization temperature to be preferably 280 to 310°C, more preferably 280 to 300°C, and even more preferably 285 to 295°C. The stabilization temperature does not need to be constant, and may be set at multiple stages. In order to increase the strand strength of the obtained carbon fiber, it is preferable to set the stabilization temperature high and the stabilization time short.

[0042] In the present invention, flame retardation refers to heat treating the precursor fiber at 200 to 310° C. in an oxygen-containing atmosphere.

[0043] The flame-resistant time described here means the time during which the fiber is retained in the flame-resistant furnace. The flame-resistant fiber means the fiber after the flame-resistant process and before the preliminary carbonization process. The peak intensity described here means the absorbance at each wavelength after baseline correction of the spectrum obtained by sampling a small amount of the flame-resistant fiber and measuring the infrared spectrum, and peak division is not performed. The sample concentration when measuring the infrared spectrum is diluted with KBr to 0.67 mass%. In this way, the infrared spectrum is measured every time the flame-resistant condition setting is changed, and the conditions are examined according to the preferred manufacturing method described later. By appropriately controlling the infrared spectrum peak intensity ratio of the flame-resistant fiber, the strand strength of the obtained carbon fiber can be controlled.

[0044] The total treatment time of the flame-resistant process can be appropriately selected preferably within the range of 13 to 20 minutes. In addition, for the purpose of improving the strand strength of the obtained carbon fiber, the treatment time of the flame-resistant process is set so that the specific gravity of the obtained flame-resistant fiber is preferably in the range of 1.28 to 1.32, more preferably 1.30 to 1.32. A more preferable treatment time of the flame-resistant process depends on the flame-resistant temperature. If the specific gravity of the flame-resistant fiber is not 1.28 or more, the strand strength of the carbon fiber may decrease. If the specific gravity of the flame-resistant fiber is 1.32 or less, the strand strength can be increased. The specific gravity of the flame-resistant fiber is controlled by the treatment time of the flame-resistant process and the flame-resistant temperature. In addition, the timing of switching from the first flame-resistant process to the second flame-resistant process is preferably set so that the specific gravity of the fiber is in the range of 1.21 to 1.23. In this case, the conditions of the flame-resistant process are controlled by giving priority to satisfying the range of the infrared spectrum intensity ratio. The preferred ranges of the flame-proofing treatment time and temperature vary depending on the characteristics of the precursor fiber and the copolymer composition of the polyacrylonitrile-based polymer.

[0045] In the pre-carbonization step of pre-carbonizing the fiber bundle obtained in the flame-retardant process, the obtained flame-retardant fiber is heat-treated in an inert atmosphere at a maximum temperature of 500 to 1,200°C until the specific gravity is preferably 1.5 to 1.8. The draw ratio in the pre-carbonization step is preferably 1.16 to 1.25. If the draw ratio in the pre-carbonization step is 1.16 or more, the strand elastic modulus is likely to be increased, and the strand strength is likely to be increased. If the draw ratio in the pre-carbonization step is 1.25 or less, the strand elastic modulus is likely to be suppressed to 300 GPa or less.

[0046] The pre-carbonized fiber is carbonized in an inert atmosphere, preferably at a maximum temperature of 1,000 to 1,500° C., more preferably at a maximum temperature of 1,100 to 1,300° C., and even more preferably at a maximum temperature of 1,150 to 1,250° C. The maximum temperature in the carbonization step is preferably lower from the viewpoint of increasing the elongation of the resulting carbon fiber, but if it is too low, the strand strength may decrease, and therefore it is preferable to set the maximum temperature taking both into consideration.

[0047] The treatment time X at the highest temperature in the carbonization step is preferably 20 to 60 seconds, more preferably 20 to 38 seconds. The treatment time X at the highest temperature in the carbonization step refers to the time required for the fiber to pass through the section in the carbonization furnace that has the highest temperature. The carbonization furnace often has multiple sections that are controlled so that the temperature is raised stepwise by heater blocks. Each section is considered to have a constant temperature for calculation. The shorter the treatment time at the highest temperature, the lower the strand modulus can be controlled, so the treatment time X is preferably 60 seconds or less. If the treatment time X is 20 seconds or more, a stable strand modulus is easily obtained.

[0048] The temperature rise rate Y in the carbonization step is preferably 0.40 to 1.1°C / sec, more preferably 0.40 to 1.0°C / sec, and even more preferably 0.40 to 0.60°C / sec. The temperature rise rate in the carbonization step affects the desorption rate of the decomposition gas, and therefore affects the strand strength. In the present invention, the temperature rise rate is defined as the average temperature rise rate per second at which the fiber passes through the area where the temperature of the section exceeds 1,000°C when the fiber passes through a plurality of sections in the carbonization furnace, which are controlled so that the temperature rises stepwise. Specifically, for example, if the fiber passes through the section with a temperature of 1,000°C in the carbonization furnace in 100 seconds before reaching the next section with a temperature of 1,100°C, the temperature rise rate is 1.0°C / sec. In another example, if the fiber passes through the section in the carbonization furnace with a temperature of 950°C in 200 seconds before reaching the next section with a temperature of 1,150°C, the heating rate is 1.0°C / sec. If the maximum temperature of the carbonization process is set to less than 1,100°C, the heating rate up to the maximum temperature is utilized. That is, if the maximum temperature is 1,050°C, if the fiber passes through the section in the carbonization furnace with a temperature of 1,000°C in 50 seconds before reaching the next section with a temperature of 1,050°C, the heating rate is 1.0°C / sec. The temperature of the first section in the carbonization furnace is preferably 1,000°C or less. If the heating rate is 0.40°C / sec or more, the strand modulus is easily obtained stably. If the heating rate is within 1.1°C / sec, the decrease in strand strength is easily suppressed.

[0049] The treatment time X and the temperature rise rate Y of the maximum temperature in the carbonization step are preferably in the range of 0.015X≦Y≦0.015X+0.6. This formula was derived from the inventor's investigation into how to increase the elongation of carbon fibers. By adjusting the treatment time X and the temperature rise rate Y to have such a relationship, it is easy to increase the elongation of carbon fibers.

[0050] The carbon fiber obtained as described above is preferably further subjected to an electrolytic surface treatment to introduce oxygen-containing functional groups. For the electrolytic surface treatment, any of gas phase oxidation, liquid phase oxidation, and liquid phase electrolytic oxidation can be used, but from the viewpoint of high productivity and uniform treatment, liquid phase electrolytic oxidation is preferably used. In the present invention, there is no particular restriction on the method of liquid phase electrolytic oxidation, and it may be performed by a known method.

[0051] After the electrolytic surface treatment, the carbon fibers may be subjected to a sizing treatment in order to impart bundling properties to the resulting carbon fibers. As the sizing agent, a sizing agent having good compatibility with the matrix resin used in the carbon fiber composite material may be appropriately selected depending on the type of matrix resin used.

[0052] Next, the carbon fiber composite material of the present invention will be described. The carbon fiber composite material of the present invention contains the above-mentioned carbon fiber of the present invention and a matrix resin.

[0053] The carbon fibers preferably used in the present invention may be continuous or discontinuous fibers, and the content of carbon fibers in the carbon fiber composite material is preferably 15 to 65% by volume.

[0054] The matrix resin used in the carbon fiber composite material of the present invention may be a thermosetting resin or a thermoplastic resin.

[0055] Examples of the thermosetting resin that can be suitably used in the present invention include epoxy resin, vinyl ester resin, phenol resin, unsaturated polyester resin, etc. Any resin that undergoes a crosslinking reaction due to heat and forms at least a partial three-dimensional crosslinked structure can be used.

[0056] An example of a molding substrate for forming a carbon fiber composite material is a prepreg. The thermosetting resin in the prepreg is preferably in a semi-cured state with excellent tackiness, since the prepregs need to be pressure-bonded to each other or to a mold when stacking the prepregs. Among these, epoxy resin is preferred in consideration of the tackiness in the process of attaching the prepregs and the mechanical properties when the molded product is formed.

[0057] Methods for molding carbon fiber composite materials using thermosetting resins include autoclave molding of prepregs, resin transfer molding of preforms such as woven fabrics, and filament winding molding.

[0058] The thermoplastic resin preferably used in the present invention is at least one thermoplastic resin selected from the group consisting of polyolefin, polyamide, polyester, polycarbonate, and polyarylene sulfide. From the viewpoint of the impact resistance of the obtained carbon fiber composite material, polyamide and polyarylene sulfide are more preferable. By combining with the carbon fiber of the present invention, the impact resistance of the obtained carbon fiber composite material can be increased without being restricted by the type of thermoplastic resin, so that the thermoplastic resin can be selected from a wide range.

[0059] In molding a carbon fiber composite material using a thermoplastic resin, the carbon fiber bundles and the thermoplastic resin are integrated by a known method such as melt impregnation, melt kneading, or slurry impregnation, and then the integrated carbon fiber bundles may be used as continuous fibers or may be cut into a fixed length of 1 to 50 mm using a device such as a pelletizer or strand cutter and used as discontinuous fibers.

[0060] The final carbon fiber composite material can be obtained by molding a continuous fiber tape or a discontinuous fiber substrate made of carbon fiber bundles and a thermoplastic resin. For example, the carbon fiber composite material can be produced by a known molding method such as press molding, injection molding, injection compression molding, compression molding, vacuum molding, or extrusion molding.

[0061] The methods for measuring various physical properties used in the present invention are as follows.

[0062] <Total fineness> A 10 m length of carbon fiber is sampled and completely dried at 120°C for 2 hours. The measured mass is then divided by 10 to determine the total fineness, which is the mass per meter.

[0063] <density> The carbon fiber to be measured is dried at 120℃ for 2 hours before measurement. A dry automatic density meter is used to measure the density, with nitrogen as the measurement medium and a 10cc sample container, and the sample volume is adjusted to 3-6cc. Measurements are performed three times, and the average value is used. In this measurement, an Accupic 1330 dry automatic density meter manufactured by Shimadzu Corporation was used.

[0064] <Single fiber diameter> It is calculated from the obtained total fineness and density and the number of filaments of the carbon fiber used in the measurement.

[0065] <Strand strength, strand modulus, elongation> The strand strength, strand modulus and elongation of the carbon fiber are determined according to the following procedure in accordance with the resin impregnated strand test method of JIS R7608:2004. The resin formulation is "Celloxide" (registered trademark) 2021P (manufactured by Daicel Chemical Industries, Ltd.) / boron trifluoride monoethylamine (manufactured by Tokyo Chemical Industry Co., Ltd.) / acetone = 100 / 3 / 4 (parts by mass), and the curing conditions are normal pressure, temperature 125 ° C, and time 30 minutes. The strand strength, strand modulus and elongation of 10 strands of carbon fiber are measured, and the average value is used. The strain range when calculating the strand modulus is 0.1 to 0.6%.

[0066] <Distortion energy density> The strain energy density is calculated by the following formula. Strain energy density (J / mm 3) = strand strength (GPa) × 1,000 × elongation (%) / 100 / 2.

[0067] <Impact resistance of carbon fiber composite materials> The carbon fiber to be tested is melt-kneaded with polyphenylene sulfide resin ("TORELINA" (registered trademark) M2888 manufactured by Toray Industries, Inc.) which is a thermoplastic resin, in a mass ratio of 30:70, and pelletized. The obtained pellets are injection molded to prepare ISO dumbbell test pieces as molded products. A parallel portion of the ISO dumbbell test piece is cut out, and a V-notched Charpy impact test is carried out in accordance with ISO 179 (2010) using a C1-4-01 model testing machine manufactured by Tokyo Test Instruments Co., Ltd., to measure the impact strength (kJ / m 2 ) is calculated and the impact resistance is evaluated and judged using the following indexes. 1: Impact strength is 13kJ / m 2 End 2: Impact strength is 12kJ / m 2 More than 13kJ / m 2 less than 3: Impact strength is 11kJ / m 2 More than 12kJ / m 2 less than 4: Impact strength is 11kJ / m 2 less than EXAMPLES

[0068] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these.

[0069] [Example 1] A spinning solution containing a polyacrylonitrile copolymer and dimethyl sulfoxide as a solvent was discharged from a spinneret into the air and then introduced into a coagulation bath consisting of an aqueous solution of dimethyl sulfoxide to obtain coagulated yarns by a dry-wet spinning method.

[0070] The solidified yarn was washed with water in a conventional manner, and then stretched 3.5 times in a two-tank warm water bath. Next, an amino-modified silicone-based silicone oil was applied to the fiber bundle after this water bath stretching, and a drying and densifying treatment was performed using a heated roller at 160°C. After making the number of single fibers 12,000, the fiber bundle was stretched 3.7 times in pressurized steam to make the total spinning stretch ratio 13 times, and then an entanglement treatment was performed to obtain a carbon fiber precursor fiber bundle with a crystal orientation degree of 93% and a number of single fibers of 12,000. The single fiber fineness of the carbon fiber precursor fiber bundle was 0.7 dtex.

[0071] Next, the first flame-stabilizing step was performed under conditions of a flame-stabilizing temperature of 250°C and a flame-stabilizing time of 11 minutes, and the second flame-stabilizing step was performed under conditions of a flame-stabilizing temperature of 280°C and a flame-stabilizing time of 6 minutes, while the carbon fiber precursor fiber bundle was stretched at a draw ratio of 1 in an oven in an air atmosphere, to obtain a flame-stabilized fiber.

[0072] 1,370 cm in the infrared spectrum of the fiber after the first flame retardant treatment -1 Peak intensity at 1,453 cm -1 The ratio of the peak intensities at 1,370 cm in the infrared spectrum of the fiber after the second flame retardant treatment was 1.04. -1 Peak intensity at 1,453 cm -1 The peak intensity ratio is 0.70 and 1,370 cm -1 Peak intensity at 1,254 cm -1 The peak intensity ratio was 0.61.

[0073] The obtained flame-retardant fiber was subjected to a pre-carbonization treatment in a nitrogen atmosphere at a maximum temperature of 800°C with a draw ratio of 1.20 to obtain a pre-carbonized fiber. The obtained pre-carbonized fiber was subjected to a carbonization treatment in a nitrogen atmosphere at a maximum temperature of 1,200°C with a draw ratio of 0.950. The temperature rise rate in the carbonization process was 0.45°C / sec. The obtained carbon fiber was subjected to a surface treatment and a sizing agent coating treatment to obtain the final carbon fiber, whose physical properties are shown in Table 1.

[0074] [Examples 2 to 11, Comparative Examples 1 to 7] Carbon fibers were obtained in the same manner as in Example 1, except that the draw ratio in the preliminary carbonization step, and the draw ratio, maximum temperature, treatment time at the maximum temperature, and temperature rise rate in the carbonization step were changed to those shown in Table 1. The obtained physical properties are shown in Table 1.

[0075] [Reference examples 1~3] A flame-resistant fiber was obtained in the same manner as in Example 1, except that the first flame-resistant step was performed under conditions of a flame-resistant temperature of 240°C and a flame-resistant time of 82 minutes, and the second flame-resistant step was performed under conditions of a flame-resistant temperature of 250°C and a flame-resistant time of 85 minutes.

[0076] 1,370 cm in the infrared spectrum of the fiber after the first flame retardant treatment -1 Peak intensity at 1,453 cm -1 The ratio of the peak intensities at 1,370 cm in the infrared spectrum of the fiber after the second flame retardant treatment was 0.68. -1 Peak intensity at 1,453 cm -1 The peak intensity ratio is 0.50 and 1,370 cm -1 Peak intensity at 1,254 cm -1 The peak intensity ratio was 0.56.

[0077] The obtained flame-retardant fiber was pre-carbonized in a nitrogen atmosphere with a maximum temperature of 800°C and a draw ratio of 1.17 to obtain a pre-carbonized fiber. The obtained pre-carbonized fiber was carbonized in a nitrogen atmosphere at the maximum temperature and time shown in Table 1, and at a draw ratio of 0.980. The temperature rise rate in the carbonization process was 0.35°C / sec. The physical properties of the final carbon fiber obtained by subjecting the obtained carbon fiber to a surface treatment and a sizing agent coating process are shown in Table 1. It was found that the strand strength does not change significantly just by changing the maximum temperature of the carbonization process, which is generally used to adjust the strand modulus, and that when the strand strength level is at a high level, it is necessary to finely adjust the conditions of the pre-carbonization process and the carbonization process shown in this example.

[0078] [Table 1] [Industrial Applicability]

[0079] The carbon fiber of the present invention allows carbon fiber composite materials having high impact resistance and large energy absorption to be obtained with high productivity.

Claims

1. Strand elastic modulus is 240 to 300 GPa, elongation is 2.65% or more, and strain energy density is 95 J / mm 3 That's all for carbon fiber.

2. 2. The carbon fiber according to claim 1, having a single fiber diameter of 4.0 μm or more.

3. The carbon fiber according to claim 2, having a single fiber diameter of 5.0 μm or more.

4. The carbon fiber according to any one of claims 1 to 3, having an elongation of 2.75% or more.

5. The carbon fiber according to claim 4, having an elongation of 2.85% or more.

6. The carbon fiber according to any one of claims 1 to 5, having a strand strength of 7.5 GPa or more.

7. Strain energy density is 100 J / mm 3 The carbon fiber according to any one of claims 1 to 6.

8. The polyacrylonitrile-based carbon fiber precursor fiber was subjected to infrared spectroscopy at 1,370 cm -1 1,453 cm -1 A first flame-stabilizing step of flame-stabilizing the sample for 8 to 25 minutes until the ratio of the peak intensities of the samples is in the range of 0.98 to 1.10; The fiber obtained in the first flame retardant treatment step was subjected to infrared spectroscopy at 1,370 cm -1 1,453 cm -1 The ratio of the peak intensities of the two peaks is in the range of 0.70 to 0.75, and the peak intensity of the two peaks is 1,370 cm -1 The peak intensity at 1,254 cm -1 A second flame-stabilizing step of flame-stabilizing the sample for 5 to 14 minutes until the ratio of the peak intensities of the above peaks is in the range of 0.50 to 0.65; a pre-carbonization step of pre-carbonizing the fiber obtained in the second flame-resistant treatment step in an inert atmosphere having a maximum temperature of 500 to 1,200° C. and a draw ratio of 1.16 to 1.25; a carbonization step of carbonizing the fiber obtained in the pre-carbonization step in an inert atmosphere at a maximum temperature of 1,000 to 1,500° C. under conditions of a treatment time X at the maximum temperature of 20 to 60 seconds and a heating rate Y of 0.40 to 1.1° C. / second; and a step of electrolytically surface treating the fiber obtained in the carbonization step to obtain carbon fiber.

9. A carbon fiber composite material comprising the carbon fiber according to any one of claims 1 to 7 and a matrix resin.

Citation Information

Patent Citations

  • Carbon fiber and its production

    JP1999152626A

  • Carbon fiber, precursor fiber for carbon fiber, composite material and production of carbon fiber

    JP1999241230A

  • Carbon fiber having high strength and high elongation, and forming material of the same

    JP2002069754A

  • Method for producing carbon fiber

    JP2004197278A

  • Carbon fiber, acrylonitrile-based precursor fiber for the same, and method for producing the carbon fiber and the precursor fiber

    JP2004211240A

Cited By

  • Carbon fiber composite material

    JP2023043149A